Sequencing the extrachromosomal circular mobilome reveals retrotransposon activity in plants. - Sophie Lanciano; Marie-Christine Carpentier; Christel Llauro; Edouard Jobet; Dagmara Robakowska-Hyzorek; Eric Lasserre; Alain Ghesquière; Olivier Panaud; Marie Mirouze (PLoS Genetics)
Retrotransposons are mobile genetic elements abundant in plant and animal genomes. While efficiently silenced by the epigenetic machinery, they can be reactivated upon stress or during development. Their level of transcription not reflecting their transposition ability, it is thus difficult to evaluate their contribution to the active mobilome. Here we applied a simple methodology based on the high throughput sequencing of extrachromosomal circular DNA (eccDNA) forms of active retrotransposons to characterize the repertoire of mobile retrotransposons in plants. This method successfully identified known active retrotransposons in both Arabidopsis and rice material where the epigenome is destabilized. When applying mobilome-seq to developmental stages in wild type rice, we identified PopRice as a highly active retrotransposon producing eccDNA forms in the wild type endosperm. The mobilome-seq strategy opens new routes for the characterization of a yet unexplored fraction of plant genomes.